Aniconism in the second commandment of the Decalogue in Exodus 20:4-6 and its inner-biblical interpretations in the Old Testament : an exegetical and theological study of Exodus 20:4-6, Exodus 32:1-6 and Isaiah 40:18-20 - Venter, P.M. (Pieter Michiel), 1947- (University of Pretoria, 2013)
Thesis (PhD)--University of Pretoria, 2011.